Integration of the two methods of production on time and accelerated implementation and their role in reducing costs - Ali Osama Talib; Raed Majeed Abed Muhammed; Ilham Salman Yousef (Journal of Madenat Alelem University College, 2022)
The Iraqi markets witnessed a great momentum in the volume of products, which led to a rise in competition, as local production requires restructuring and the adoption of new systems that will raise competitiveness in the market. The main research problem is the time period required for production and inventory and its costs, where the time of products exceeds the planned time.The research seeks to apply the method of production on time and accelerated implementation to shorten the production period, cancel inventory of all kinds (raw materials, semi-manufactured, finished) and rearrange the factory to ensure shortening the distances between the factory machines and shortening the transportation time and thus accelerating the production process and indicating the sites of weakness within the unit  In addition to developing appropriate and feasible solutions in industrial units to enable them to monitor the implementation stages, solve the problems they face and measure the time required in each stage of work in order to rationalize costs and increase the number of products,the research seeks in its applied side to prove the research hypothesis that  adjusting the production process in order to reduce industrial costs, which leads to identifying waste areas in all stages of production and then finding temporal and cost deviations at any stage of the project and analyzing them to rationalize the costs of those paragraphs. In/11  2021 until 07/2022 the field of application of the research and the two production methods were used on time  and the accelerated implementation within the production line of the Rafidain breeze fan, and the identification of waste areas and the method and their treatment, and one of the most important conclusions of the research is the possibility of reducing costs significantly by eliminating all kinds of waste.